REGRESI PANEL SPASIAL: HUBUNGAN TRANSPORTASI DAN TATA RUANG TERHADAP PERTUMBUHAN KENDARAAN DI KALIMANTAN TIMUR - Amalia Nindya Kartika (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2026)
The relocation of Indonesia’s Capital City (IKN) to East Kalimantan presents challenges in managing the linkage between land use and transportation systems. Changes in land use and the increase in motor vehicle ownership may potentially lead to transportation and environmental problems. This study aims to analyze the influence of transportation factors and regional dynamics on the number of motor vehicles in East Kalimantan. This research employs a quantitative approach using panel data regression based on secondary data from 2018–2023 at the regency/city level. The independent variables include road length, total and population growth, economic growth, and the area of built-up and non-built-up land, while the dependent variable is the number of motor vehicles. Model selection was conducted through panel data regression testing, and the results indicate that the Random Effect Model (REM) is the most appropriate model. Partially, only the built-up area (LCT) has a significant effect on the number of motor vehicles, while the other variables are not statistically significant. However, the simultaneous test (F-test) shows that all independent variables collectively have a significant effect on the number of motor vehicles, with a coefficient of determination (R² = 0.4473). These findings highlight that the growth of built-up areas plays a crucial role in increasing motor vehicle numbers in East Kalimantan. Therefore, the integration of spatial planning and transportation systems is essential to support sustainable IKN development.